AN ANALYSIS OF LANGUAGE STYLE USED BY KIM NAMJOON IN HIS SPEECH IN UNITED NATIONS AT THE 2030 YOUTH EVENT IN 2018 - MIFTAHUL JANNAH; YANTO; NUR SYAMSIYAH EKHSAN (CV KULTURA DIGITAL MEDIA, 2023)
This paper entitled